A dual modal silver bumpy nanoprobe for photoacoustic imaging and SERS multiplexed identification of in vivo lymph nodes. Issue 34 (18th August 2017) - Cha, Myeong Geun; Lee, Seunghyun; Park, Sungjo; Kang, Homan; Lee, Sung Gun; Jeong, Cheolhwan; Lee, Yoon-Sik; Kim, Chulhong; Jeong, Dae Hong
Abstract : Overall photographs of in vivo PA imaging and multiplexed detection using SERS with silver bumpy nanoshells (AgNS@SiO2 ). Abstract : Multimodal imaging can provide complementary biomedical information which has huge potential in pre-clinical and clinical imaging and sensing. In this study, we introduce dual modal NIR silver bumpy nanoprobes for in vivo imaging and multiplexed detection of biomolecules by both photoacoustic imaging (PAI) and surface-enhanced Raman scattering (SERS) techniques. For this study, we used silica-coated silver bumpy nanoshell probes (AgNS@SiO2 ). AgNS@SiO2 have strong NIR-absorption and scattering properties compared with other nanostructures, and therefore, can be a good candidate for photoacoustic (PA) and SERS multimodal imaging. We obtained PA images of the skin and SLNs of rats by injecting various kinds of Raman-labeled AgNS@SiO2 . Multiplexed identification of the injected AgNS@SiO2 was achieved by measuring SERS signals. AgNS@SiO2 have the potential to be applied in detecting cancer biomarkers by locating biomarkers quickly using PA imaging, and identification by multiplexed target measurement using SERS signals in vivo .